(untitled) (Journal of the College of Languages (JCL), 2025)
The present study focuses on the complex relationship between neurotic personality traits and criminal behavior as illustrated in Deep Water. It examines the protagonist, Vic Van Allen, and his descent into criminality using the social psychological framework of Karen Horney’s Theory of Neurotic Personality (1950). Such examination analyzes how his deep insecurities, heightened anxiety, paranoia, and pathological relationship gradually contribute to his involvement in criminological acts. Additionally, it sheds light on how negative external factors and social constraints increase his internal conflicts and trigger his criminological behavior. Amidst these complexities, the protagonist struggles to maintain a façade of self-esteem and an illusion of an ideal suburban life in America, navigating the slight balance between social acceptance and deviant behavior. This study reveals the complex relationship between the neurotic traits and criminal behavior in both literary portrayals and real-world contexts by examining the protagonist’s involvement in criminal activities within the framework of marital relations and social interactions.